Engineering geological evaluation of Mfensi and Afari clay deposits for liner applications in municipal solid waste containment systems - Endene, Che Emmanuel (2016)
A Thesis Submitted to the Department of Geological Engineering, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Philosophy (GEOLOGICAL ENGINEERING) College of Engineering Department of Geological Engineering.